Clonal interference and genomic repair during strain coexistence in the gut. - Nelson Frazão; Elsa Seixas; Manolo Mischler; Jorge Moura-de-Sousa; Hugo C Barreto; Isabel Gordo (PLoS Genetics)
Humans and other mammals are colonized by multiple strains of Escherichia coli, but the tempo and mode of evolution of different coexisting strains, between whom horizontal gene transfer (HGT) can occur, is poorly understood. Here, we follow in real time the evolution of two phylogenetic distinct strains of E. coli that co-colonize the mouse gut with different population sizes. We find qualitative differences in evolutionary dynamics between strains within the same host. In the strain with larger population size intense clonal interference occurs and polymorphism at a neutral marker locus is maintained, while in the strain with lower population size complete selective sweeps and loss of neutral marker polymorphism occurs. Strain coexistence is also accompanied by rich dynamics of HGT from one strain to the other. Strikingly, a rare HGT event could restore a previously lost genomic region in the recipient strain. Furthermore, we detect for the first time a case of phage piracy in the gut, where a putative phage satellite, lacking essential genes for their own replication, was likely mobilized by a helper phage to transfer between bacterial hosts. Our results show that HGT is a key mechanism underlying genetic exchanges and adaptive genomic repair in the mammalian gut.